European Hedgehogs as Hosts of Chaphamaparvovirus, Italy - Federica Di Profio; Barbara Di Martino; Gianvito Lanave; Serena Robetto; Ilaria Prandi; Maria Teresa Capucchio; Maria Lucia Mandola; Giuseppe Quaranta; Riccardo Orusa; Fulvio Marsilio; Vito Martella; Vittorio Sarchese (Animals)
In 2022, a novel parvovirus was identified from an outbreak of fatal enteritis in weaned European hedgehogs (Erinaceus europaeus) at a wildlife rescue center in Southern Italy. During sequence analysis, the strain was found to be closely related (90.4% nucleotide identity) to a chaphamaparvovirus (ChPV) discovered in Amur hedgehogs (Erinaceus amurensis) during a large metaviromic investigation in game animals in China. In this study, we investigated the presence of this novel ChPV in necropsied European hedgehogs from different areas of North-Western Italy. Duodenal and liver samples collected from 194 necropsied hedgehogs were screened by using a specific quantitative PCR. A total of 38/194 animals (19.6%) tested positive, with ChPV DNA being detected in the duodenum (9.3%, 18/194), liver (7.2%, 14/194) or in both (3.1%, 6/194) tissue samples, with comparable rates and mean viral loads. The nearly full-length genome of four hedgehog ChPV strains was reconstructed. During phylogenetic analysis based on the NS1 and partial VP aa sequences, the four strains detected in this study tightly clustered with the prototype ChPVs previously identified in Amur and European hedgehogs within a potential novel candidate species of the genus Chaphamaparvovirus.